Peran Orang tua Dalam Melakukan Imunisasi Dasar Pada Bayi Usia 0-12 Bulan di Posyandu Wilayah Kerja Puskesmas Payung Sekaki - Wiwik Norlita; Isnaniar; Tasya Susmaya Putri (As-Shiha: Jurnal Kesehatan, 2024)
Basic immunization is the initial immunization given to infants before one year of age. In this condition, it is expected that the immune system can work optimally. Every infant (age 0-12 months) is required to get complete basic immunization consisting of 1 dose of Hepatitis B, 1 dose of BCG, 3 doses of DPT-HB-HiB, 4 doses of polio drops, and 1 dose of measles or MR. Objective: To determine the role of parents in performing basic immunization for infants aged 0-12 months at the Posyandu of the Payung Sekaki Health Center Working Area, Pekanbaru City. Research Methods: This type of research is descriptive. This research was conducted on 17 to 27 June 2023 at the Posyandu of the Payung Sekaki Health Center Working Area, The population in this study was taken from the number of visits by parents who took babies 0-12 months to the posyandu of the umbrella sekaki health center working area with the number of respondents used was 61 respondents. The sampling technique used is Accidental sampling technique is the process of taking respondents to be sampled based on samples that happen to meet with researchers. Then respondents who feel suitable are used as data sources. The instrument used in this research is a questionnaire using a Likert scale, namely choosing one of the two alternative answers tailored to the subject's situation. Research Results: Shows the role of parents in performing basic immunization in infants aged 0-12 months in the posyandu working area of the umbrella sakaki health center in Pekanbaru city. The majority of parents played a role, namely with respondents. Conclusion: Based on the results of the research that has been done, it can be concluded that the role of parents is very important to carry out basic immunization in infants aged 0-12 months in the posyandu of the umbrella sekaki health center working area.